A protocol for applying health equity-informed implementation science models and frameworks to adapt a sleep intervention for adolescents at risk for suicidal thoughts and behaviors - Williamson, Ariel A.; Soehner, Adriane M.; Boyd, Rhonda C.; Buysse, Daniel J.; Harvey, Allison G.; Jonassaint, Charles R.; Franzen, Peter L.; Goldstein, Tina R. (Frontiers in Public Health, 2022)
Background Effective and equitable strategies to prevent youth suicidal thoughts and behaviors (STB) are an urgent public health priority. Adolescent sleep disturbances are robustly linked to STB but are rarely addressed in preventive interventions or among Black and/or Hispanic/Latinx youth for whom STB risk is increasing disproportionately. This paper describes an application of health equity-informed implementation science models and frameworks to adapt and evaluate the evidence-based Transdiagnostic Sleep and Circadian (TSC) intervention for primary care implementation with adolescents of minoritized backgrounds with depression and STB risk. Methods This multiphase study protocol uses the Assessment, Decision, Adaptation, Production, Topical Experts-Integration, Training, Testing (ADAPT-ITT) model to adapt and evaluate TSC for primary care implementation with adolescents who are depressed, at risk for STB, and of primarily Black and/or Hispanic/Latinx backgrounds. We integrate the Consolidated Framework for Implementation Research (CFIR) in an initial qualitative inquiry of adolescent, caregiver, and clinician perceptions of TSC. Subsequent ADAPT-ITT phases include systematically and iteratively testing adaptations based on the qualitative inquiry, with ongoing key informant input, and then evaluating the adapted TSC for feasibility, acceptability, and efficacy in a pilot randomized trial. Anticipated results Based on youth depression and sleep health disparities research, we expect that TSC adaptations will be needed to enhance intervention content for adolescents with depression, STB risk, and primarily Black and/or Hispanic/Latinx backgrounds. We also anticipate adaptations will be needed to align TSC delivery methods with primary care implementation. Conclusions Adapting evidence-based interventions with end-users and contexts in mind can help ensure that intervention strategies and delivery methods are acceptable to, and feasible with, health disparate populations. Although TSC has shown effectiveness for adolescents with sleep disturbances, we expect that additional multiphase research is necessary to optimize TSC for primary care delivery with Black and/or Hispanic/Latinx adolescents with depression and STB risk.